2022
DOI: 10.1039/d2cp00886f
|View full text |Cite
|
Sign up to set email alerts
|

Comparative electron irradiations of amorphous and crystalline astrophysical ice analogues

Abstract: We have irradiated the amorphous and crystalline phases of CH3OH and N2O astrophysical ice analogues using 2 keV electrons and have found that the decay rate is dependent upon the nature and extent of the intermolecular bonding in these solid phases.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 84 publications
(203 reference statements)
6
16
0
Order By: Relevance
“…Similar trends for O 2 and H 2 production were observed by Zheng et al who made use of quadrupole mass spectrometry to detect the formation of these products in electron irradiated ASW and Ic [45]. Such results are further evidence that the phase and structural morphology of an astrophysical ice analogue has a direct influence on its radiolytic chemical productivity [45,46].…”
Section: Comparative H 2 O 2 Productivitiessupporting
confidence: 81%
See 3 more Smart Citations
“…Similar trends for O 2 and H 2 production were observed by Zheng et al who made use of quadrupole mass spectrometry to detect the formation of these products in electron irradiated ASW and Ic [45]. Such results are further evidence that the phase and structural morphology of an astrophysical ice analogue has a direct influence on its radiolytic chemical productivity [45,46].…”
Section: Comparative H 2 O 2 Productivitiessupporting
confidence: 81%
“…Our work therefore represents a progression in our understanding of the phase dependence of the radiation physics and chemistry of H 2 O astrophysical ices, thus allowing this parameter to be better incorporated into more exhaustive and relevant future experiments performed using a systems astrochemistry approach [47]. We have also interpreted our results in light of the new conclusions presented by Mifsud et al with regards to the role of hydrogen-bonds in impeding the radiolytic decay of crystalline ices [46].…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Our recent work has also demonstrated that the solid phase of an irradiated ice plays a crucial role in determining the outcome of astrochemical reactions mediated by ionising radiation. Through a series of comparative electron irradiations, we have demonstrated that the radiolytic decay rate of an astrochemical ice is dependent upon the nature, strength, and extent of the intermolecular interactions that characterise its solid phase ( Mifsud et al, 2022b ; Mifsud et al, 2022c ). For instance, the decay rate of α-crystalline CH 3 OH was found to be significantly less rapid than that of the amorphous phase.…”
Section: Introductionmentioning
confidence: 99%